2015
DOI: 10.4172/2155-6156.1000634
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Glucose Disposal and Insulin Signaling in Pregnant Mice Fed a High Fat Diet

Abstract: Objective-Physical activity has been suggested as a non-pharmacological intervention that can be used to improve glucose homeostasis in women with gestational diabetes mellitus. The purpose of this study was to determine the effects of voluntary exercise on glucose tolerance and body composition in pregnant high fat diet fed mice.Methods-Female mice were put on a standard diet or high fat diet for two weeks. The mice were then split into 4 groups; control standard diet fed, exercise standard diet fed, control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…14 In the rodent literature there are two methods commonly employed to mimic exercise: voluntary wheel-running where animals are given free access to a running-wheel, or forced exercise through treadmills or motorized running-wheels. Both voluntary wheel-running 15,16 and forced exercise 17,18 are effective in improving health and reducing obesity in rodents fed a high-fat diet; however, these animals were still overweight and exhibited more unhealthy characteristics than sedentary animals on low-fat diets (low-fat diet). Switching high-fat diet fed rodents to a low-fat diet can promote weight loss, 19 but there is some evidence showing that these animals may not fully recover from the obesogenic effects of the high-fat diet and remain heavier than their low-fat diet controls even after the high-fat diet is removed.…”
Section: Introductionmentioning
confidence: 99%
“…14 In the rodent literature there are two methods commonly employed to mimic exercise: voluntary wheel-running where animals are given free access to a running-wheel, or forced exercise through treadmills or motorized running-wheels. Both voluntary wheel-running 15,16 and forced exercise 17,18 are effective in improving health and reducing obesity in rodents fed a high-fat diet; however, these animals were still overweight and exhibited more unhealthy characteristics than sedentary animals on low-fat diets (low-fat diet). Switching high-fat diet fed rodents to a low-fat diet can promote weight loss, 19 but there is some evidence showing that these animals may not fully recover from the obesogenic effects of the high-fat diet and remain heavier than their low-fat diet controls even after the high-fat diet is removed.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, subjects supplemented with vitamin D have not shown any improvement in the blood glucose reduction but the values are remained unvaried. Hence, the study clearly indicates that RA patient supplemented with vitamin D has less risk of prediabetes compared to non vitamin D patients and it seems that vitamin D might maintain or improve the insulin resistance and insulin sensitivity 10 . At the same time rate of predisposition of prediabetes has reduced nearly 20% in vitamin D supplemented group as compared to non vitamin D group.…”
Section: Discussionmentioning
confidence: 99%
“…In respect to this concept few studies reported that source of vitamin D is important in regulating lipid profile. Saedisomeolia et al reported that sunlight exposure is very effective than the vitamin D supplementation 10,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive behavioral therapy has also shown positive results, while surgical procedures such as sleeve gastrectomy, gastric bypass, gastric banding, and duodenal switch are the most common bariatric approaches aimed at managing obesity (Gero et al 2017;Hanipah and Schauer 2017;Kaplan 2017;Zimbron et al 2016). One noninvasive non-pharmacological intervention is exercise (Bruyndonckx et al 2015;Carter et al 2015;Glynn et al 2015). However, it has been demonstrated that many patients are still unable to achieve a clinically meaningful improvement, since their principal motivation is based on a better appearance rather than improving their health status.…”
Section: Current Therapeutic Approaches For Managing Obesitymentioning
confidence: 99%